2013
DOI: 10.1016/j.jadohealth.2012.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Teenage Risky Driving of Feedback From a Safety Monitoring System: A Randomized Controlled Trial

Abstract: Purpose Teenage risky driving may be due to teenagers not knowing what is risky, preferring risk, or the lack of consequences. Elevated gravitational-force (g-force) events, caused mainly by hard braking and sharp turns, provide a valid measure of risky driving and are the target of interventions using in-vehicle data recording and feedback devices. The effect of two forms of feedback about risky driving events to teenagers only or to teenagers and their parents was tested in a randomized controlled trial. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 26 publications
2
52
0
Order By: Relevance
“…Evaluations of these programs have demonstrated that this feedback to teens and parents is associated with rapid declines in KRD rates and presumably improved safety, although the programs have been too small to demonstrate crash reductions. In one randomized trial, DriveCam devices were installed in the vehicles of young drivers and set on "stealth" mode for a month [8]. Then, in one group, the light was activated so the driver was informed by a blinking light when an event occurred.…”
Section: Kinematic Risky Drivingmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluations of these programs have demonstrated that this feedback to teens and parents is associated with rapid declines in KRD rates and presumably improved safety, although the programs have been too small to demonstrate crash reductions. In one randomized trial, DriveCam devices were installed in the vehicles of young drivers and set on "stealth" mode for a month [8]. Then, in one group, the light was activated so the driver was informed by a blinking light when an event occurred.…”
Section: Kinematic Risky Drivingmentioning
confidence: 99%
“…Novices have particularly high crash rates in the months just after licensure that decline rapidly for about 6 months and/or 1000 miles and then more slowly for years [3][4][5]. While novices presumably make many judgment errors due to inexperience and young age [6,7], they also experiment with risky driving behaviors [8]. Moreover, relative to older drivers, novices are easily distracted from the driving task [9].…”
Section: Introductionmentioning
confidence: 99%
“…Real-time alerts and feedback as well as post-driving summary reports can be generated and used as discussion points with driver instructors or parents. Also, seeing records of their own driving patterns provides opportunities for young drivers to reflect and think about their own behaviors and consequences (Simons-Morton et al, 2013). However, studies have reported resistance from young drivers about using such in-vehicle technologies, with them claiming that these technologies are virtual parents and are forms of privacy invasion (GesserEdelsburg & Guttman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have reported resistance from young drivers about using such in-vehicle technologies, with them claiming that these technologies are virtual parents and are forms of privacy invasion (GesserEdelsburg & Guttman, 2013). In addition, although some results are positive, such as increased seatbelt use (Farmer, Kirley, & McCartt, 2010), more complicated behaviors (e.g., speeding) are difficult to change (McCartt, Farmer, & Jenness, 2010) and the success of the intervention demanded constant support and monitoring from motivated parents (McGehee, Raby, Carney, Lee, & Reyes, 2007;Simons-Morton, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted and objective feedback can help provide information about performance, set goals for safety behaviors, help identify unsafe behaviors, and serve as a way to provide comparisons with peers. Such approaches have shown evidence of reduction in risky behaviors in other driver groups including teenage drivers (Toledo & Lotan, 2006;Simons-Morton et al, 2013).…”
mentioning
confidence: 99%